2022
DOI: 10.1038/s41467-022-29248-x
|View full text |Cite
|
Sign up to set email alerts
|

Extremely wet summer events enhance permafrost thaw for multiple years in Siberian tundra

Abstract: Permafrost thaw can accelerate climate warming by releasing carbon from previously frozen soil in the form of greenhouse gases. Rainfall extremes have been proposed to increase permafrost thaw, but the magnitude and duration of this effect are poorly understood. Here we present empirical evidence showing that one extremely wet summer (+100 mm; 120% increase relative to average June–August rainfall) enhanced thaw depth by up to 35% in a controlled irrigation experiment in an ice-rich Siberian tundra site. The e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…While such ground compaction is very common in peatlands (Batey 2009), the sandy silt soils that we found are only moderately compressible (Akayuli et al, 2013;Halcomb and Sjostedt 2019), especially as they were frozen throughout a major time of the year, making soil compaction a weak argument for the shallow active layer at intensively grazed sites. The regular flooding of the intensively grazed basin site, which usually leads to an increase in thaw depth (Magnússon et al, 2022), combined with the in fact shallower active layer found in our study when comparing to the non-grazed B1 site, suggests that the cooling effects induced by animal activity could be much larger than previously expected.…”
Section: Effects Of Grazing On Vegetation Structure and Permafrost Thawsupporting
confidence: 46%
See 2 more Smart Citations
“…While such ground compaction is very common in peatlands (Batey 2009), the sandy silt soils that we found are only moderately compressible (Akayuli et al, 2013;Halcomb and Sjostedt 2019), especially as they were frozen throughout a major time of the year, making soil compaction a weak argument for the shallow active layer at intensively grazed sites. The regular flooding of the intensively grazed basin site, which usually leads to an increase in thaw depth (Magnússon et al, 2022), combined with the in fact shallower active layer found in our study when comparing to the non-grazed B1 site, suggests that the cooling effects induced by animal activity could be much larger than previously expected.…”
Section: Effects Of Grazing On Vegetation Structure and Permafrost Thawsupporting
confidence: 46%
“…We found shallow thaw depths at intensively grazed sites and a much thicker active layer at the non-grazed B1 site. Generally, the increase in active layer thickness is associated with warming of the ground, influenced by summer temperatures, flooding, insulation from snow, and vegetation density and composition (Walker et al, 2003;Skarin et al, 2020;Magnússon et al, 2022). Therefore, as was stated by Zimov et al (2012), the direct influence on these insulating factors could affect the active layer dynamics due to a stronger cooling of the ground in winter (Figure 1).…”
Section: Effects Of Grazing On Vegetation Structure and Permafrost Thawmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, it is important to use three-dimensional mathematical models and to approve the simulation of the operation of SCDs, the efficiency of which depends on the temperature difference in the ventilated underground and the ground temperature. Effectiveness of SCDs depends on the air temperature and it will be valuable to compare the results of the presented and models of the coupling between water and heat transfer [72][73][74][75][76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…There are many approaches to solving such problems that consider the relationship between water and heat transfer and the influence of the lateral flow of groundwater [72][73][74][75][76][77][78][79][80].…”
Section: Research Objects and Methodsmentioning
confidence: 99%